The Correlation between Learning Style and Listening Achievement of English Education Study Program Students of Sriwijaya University - Zainal A. Naning; Rita Hayati (Politeknik Negeri Sriwijaya, 2011)
Abstract: The objective of this study is to find out whether or not there is a significant correlation between learning style and listening achievement of English Education Study Program Students of Sriwijaya University. The population of this study was the first semester, the third semester, the fifth semester, and the seventh semester students of English Education Study Program of Sriwijaya University in academic year 2009/2010. However, only the third and the fifth semester students were taken as the sample by using convenience sampling. A descriptive method was used in this study. Specifically, this study was a correlational study. The data were obtained by means of questionnaire and TOEFL listening test. The questionnaire showed that visual learning style was the most preferred learning style, followed by auditory learning style and kinesthetic learning style respectively. Meanwhile, the TOEFL listening test showed that most students were in Fair category (grade C). The data obtained were analyzed by using Chi-Square analysis. From the data analysis, it was found that there was no correlation between learning style and listening achievement of English Education Study Program Students of Sriwijaya University since the Chi-Square obtained (11.706) was smaller than the table value (15.507) at the significance level 0.05 and degrees of freedom of 8.